MENINGKATKAN KETERAMPILAN DASAR SHOOTING DALAM PERMAINAN BOLA BASKET MELALUI PERMAINAN BOLA TEMBAK PADA SISWA KELAS X.2 SMA NEGERI 3 PEKANBARU - wawan saputra; Haristio Anugerah; Ahmad Tri Aldo; Muhamad Rafi; Nurul Fadillah; Zulrafli; Titin Angriana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research discusses about improving the basic skills of Shooting in basketball games through shooting ball games for students in class XMIA SMA Negeri 3 Pekanbaru. This research uses qualitative research methods in the form of classrooom action research. This research method was chosen because it provides an overview of student behavior during teaching and learning activities. The result of this study is an increase in the basic skills of shooting basketball through the game of tempak balls by using tools to give a stimulus effect on the direction of the eye's view so that it can automatically focus more. In this study conducted with two cycles. Students in terms of shooting experienced good progress from the pre-cycle only obtained an average score of 5.87, increased to 7.43 at the end of cycle I and increased to 9.71 at the end of cycle II.